Constraints and Challenges of Carbon Tax Policy Implementation: Conditions and Expectations for the Future of the Green Economy in Indonesia - Ahmad Redi (Universitas Dharma Wacana, 2022)
Economic and industrial activities that are supported by fossil energy produce negative externalities in the form of carbon emissions so that they become the main cause of global warming. Government intervention is needed to mitigate carbon emissions by making policies in the form of carbon taxes. Carbon tax in Indonesia has been regulated in the Law on Harmonization of Tax Regulations and Presidential Regulation Number 98/2021. The carbon tax policy regulated in the regulation is made as a form of contribution from the state in reducing carbon emissions so that the realization of carbon emission reductions and renewables as well as the realization of a green economy. The regulation has been in effect, but the Government of Indonesia has not implemented it because of the obstacles and challenges in implementing the regulation. This research uses a normative research method with descriptive analytical research type and is supported by primary and secondary legal materials. The results of the study state that the need for coal energy due to the Russia-Ukrainian war, the unprepared infrastructure for carrying out the carbon tax, and the unstable economic condition of the Indonesian people due to the Covid-19 Pandemic are obstacles and challenges for the Indonesian Government in realizing a green economy through a carbon tax policy.